Changes in Hepatic Venous Pressure Gradient Predict Hepatic Decompensation in Patients Who Achieved Sustained Virologic Response to Interferon‐Free Therapy. Issue 3 (14th October 2019) - Mandorfer, Mattias; Kozbial, Karin; Schwabl, Philipp; Chromy, David; Semmler, Georg; Stättermayer, Albert F.; Pinter, Matthias; Hernández‐Gea, Virginia; Fritzer‐Szekeres, Monika; Steindl‐Munda, Petra; Trauner, Michael; Peck‐Radosavljevic, Markus; et al.
Abstract : Background and Aims: Sustained virologic response (SVR) to interferon (IFN)‐free therapies ameliorates portal hypertension (PH); however, it remains unclear whether a decrease in hepatic venous pressure gradient (HVPG) after cure of hepatitis C translates into a clinical benefit. We assessed the impact of pretreatment HVPG, changes in HVPG, and posttreatment HVPG on the development of hepatic decompensation in patients with PH who achieved SVR to IFN‐free therapy. Moreover, we evaluated transient elastography (TE) and von Willebrand factor to platelet count ratio (VITRO) as noninvasive methods for monitoring the evolution of PH. Approach and Results: The study comprised 90 patients with HVPG ≥ 6 mm Hg who underwent paired HVPG, TE, and VITRO assessments before (baseline [BL]) and after (follow‐up [FU]) IFN‐free therapy. FU HVPG but not BL HVPG predicted hepatic decompensation (per mm Hg, hazard ratio, 1.18; 95% confidence interval, 1.08‐1.28; P  < 0.001). Patients with BL HVPG ≤ 9 mm Hg or patients who resolved clinically significant PH (CSPH) were protected from hepatic decompensation. In patients with CSPH, an HVPG decrease ≥ 10% was similarly protective (36 months, 2.5% vs. 40.5%; P  < 0.001) but was observed in a substantially higher proportion of patients (60% vs. 24%; P  < 0.001). Importantly, the performance of noninvasive methods such as TE/VITRO for diagnosing an HVPG reduction ≥ 10% was inadequate for clinical use (area under the receiver operating characteristic curve [AUROC],  < 0.8), emphasizing the need for HVPG measurements. However, TE/VITRO were able to rule in or rule out FU CSPH (AUROC, 0.86‐0.92) in most patients, especially if assessed in a sequential manner. Conclusions: Reassessment of HVPG after SVR improved prognostication in patients with pretreatment CSPH. An "immediate" HVPG decrease ≥ 10% was observed in the majority of these patients and was associated with a clinical benefit, as it prevented hepatic decompensation. These results support the use of HVPG as a surrogate endpoint for interventions that lower portal pressure by decreasing intrahepatic resistance.